PERAN STAF TATA USAHA DALAM PENGELOLAAN SURAT MASUK DI SEKOLAH SMP TUNAS BARU CIPARAY - Santi Aprillani; Ramayani Yusuf (SECAD, 2025)
This study aims to examine the role of administrative staff in managing incoming mail at SMP Tunas Baru Ciparay. Incoming mail is a crucial component of school administration, functioning as a formal communication tool and documentation record. The research uses a descriptive qualitative method through direct observation and interviews with administrative staff. The results show that the staff plays an active role in receiving, recording, archiving, and following up on incoming correspondence. The procedures are implemented systematically, although there are challenges such as recording errors and delays in processing due to the absence of the principal. The study concludes that administrative staff have a vital role in ensuring smooth school administration and should be supported through regular training and the adoption of digital systems to improve efficiency.